A Study Of Polydadmac Induced Flocculation In Treatment Of Pulp And Paper Mills Wastewater - Razali, Mohd Amin Ahmad (2011)
This study investigates the effect of polyDADMAC on treating pulp and paper mills wastewater. PolyDADMAC was synthesized with different monomer concentration. Fourier Transform Infrared Spectroscopy (FTIR) was conducted to confirm the structure of polyDADMAC. Ubbelohde Viscometer was used to determine intrinsic viscosity and these values were used to determine molecular weight by employing the Mark Houwink equations. Molecular weight and intrinsic viscosity increased with increasing of monomer concentration (1.37 to 1.87M). Beyond the monomer concentration 1.87M the molecular weight began to decrease. Subsequently, the jar test was conducted using polyDADMAC produced on kaolin suspensions and factory wastewater.